College major choice and the gender gap - Basit Zafar (Federal Reserve Bank of New York, 2009)
Males and females are markedly different in their choice of college major. Two main reasons have been suggested for the gender gap: differences in innate abilities and differences in preferences. This paper addresses the question of how college majors are chosen, focusing on the underlying gender gap. Since observed choices may be consistent with many combinations of expectations and preferences, I use a unique data set of Northwestern University sophomores that contains the students' subjective expectations about choice-specific outcomes. I estimate a choice model where selection of college major is made under uncertainty (about personal tastes, individual abilities, and realizations of outcomes associated with the choice of major). Enjoying coursework, finding fulfillment in potential jobs, and gaining the approval of parents are the most important determinants in the choice of college major. Males and females have similar preferences while in college, but their preferences diverge in terms of the workplace: Nonpecuniary outcomes at college are most important in the decisions of females, while pecuniary outcomes realized at the workplace explain a substantial part of the choice for males. I decompose the gender gap into differences in beliefs and preferences. Gender differences in beliefs about academic ability explain a small and insignificant part of the gap, a finding that allows me to rule out low self-confidence as a possible explanation for females' underrepresentation in the sciences. Conversely, most of the gender gap is the result of differences in beliefs about enjoying coursework and differences in preferences.
Keywords: D8; I2; J1; Z1; 330; College majors; uncertainty; subjective expectations; preferences; gender differences; culture